Pengaruh Likuiditas, Leverage, Dan Arus Kas Terhadap Financial Distress - Wijaya, Jennifen; Suhendah, Rousilita (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2023)
The purpose of this study is to obtain empirical evidence regarding the effect of liquidity, leverage, and cash flow on financial distress. This study used consumer cyclicals sector companies listed on the Indonesia Stock Exchange in 2019-2021. Samples were selected by purposive sampling method and the data used were 133 data. The data obtained was processed using the E-Views 12 program. Based on the research conducted, liquidity has a positive significant effect on financial distress, leverage has a negative significant effect on financial distress, and cash flow has a positive significant effect on financial distress. The implication of this research is that liquidity, leverage, and cash flow affect company management, investors, and creditors in making decisions.